2011
DOI: 10.3382/ps.2010-01075
|View full text |Cite
|
Sign up to set email alerts
|

The chick embryo yolk sac membrane expresses nutrient transporter and digestive enzyme genes

Abstract: The yolk sac membrane plays a major role in the transport of nutrients from the yolk contents to the chick embryo. We examined whether the yolk sac membrane expresses genes for nutrient digestion, enzymes, and nutrient transporters. We evaluated relative mRNA abundance of the digestive enzymes aminopeptidase N (APN) and sucrase-isomaltase (SI); the nutrient transporters oligopeptide transporter Pept1, cationic amino acid transporter CAT1, and sodium glucose transporter SGLT1; and the micronutrient transporters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 43 publications
4
67
0
1
Order By: Relevance
“…After the digestion of the egg white and endogenous yolk proteins, they probably transfer by endocytosis or through the membrane peptide and amino acid transporters into the endodermal cells of the yolk sac as previously suggested in other avian species (Yoshizaki et al 2004;Nakazawa et al 2011;Yadgary et al 2011;Dong et al 2012;Speier et al 2012;Uni et al 2012). Then, they may reach the extraembryonic blood vessels in the mesoderm which deliver them into the developing embryo (Yoshizaki et al 2004;Nakazawa et al 2011;Sheng & Foley 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the digestion of the egg white and endogenous yolk proteins, they probably transfer by endocytosis or through the membrane peptide and amino acid transporters into the endodermal cells of the yolk sac as previously suggested in other avian species (Yoshizaki et al 2004;Nakazawa et al 2011;Yadgary et al 2011;Dong et al 2012;Speier et al 2012;Uni et al 2012). Then, they may reach the extraembryonic blood vessels in the mesoderm which deliver them into the developing embryo (Yoshizaki et al 2004;Nakazawa et al 2011;Sheng & Foley 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In chicken, this route was shown to be responsible for the major transfer of yolk into intestine on the day of hatching and several days after (Esteban et al 1991;Noy & Sklan 2001). Many of the membrane transporters that transfer the products of protein hydrolysis into the enterocytes of the intestine are also expressed in the endodermal cells of the yolk sac membrane (Yadgary et al 2011;Dong et al 2012;Speier et al 2012). These findings are not surprising because the origin of the yolk sac membrane is the hindgut of the embryo (Noble & Cocchi 1990), and thus the yolk sac membrane is expected to participate, like the intestine, in transporting nutrients into the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that lower volumes for solutions containing maltose, sucrose, or fructose should be considered for in ovo injection. liver and yolk sac membrane (Speake et al, 1998;Zhao et al, 2010;Yadgary et al, 2011). Therefore, it is not surprising that any malfunction in yolk utilization may reduce the growth of the embryo.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, we have shown that finger-like projections extended from the yolk sac membrane during development which is morphologically very similar to the placental villi found in human and mice. Angiogenesis occurs inside both avian and mammalian protrusions and is involved in nutrient and gas exchange (Yadgary et al, 2011(Yadgary et al, , 2013(Yadgary et al, , 2014. We have demonstrated that the CAM is highly vascular, and their localization underlying the egg shell ensure the gas exchange in avian.…”
Section: Discussionmentioning
confidence: 98%